Attitude formation and ethics among medical students :bstrategies adopted by the School of Medical Sciences Universiti Sains Malaysia - Zabidi Azhar Mohd Hussin (1997)
ABSTRACTS:The increasing public complaints against the medical and nursing professions and the number of cases of alleged serious misconduct amongst the medical profession can be attributed to the neglect of aspects such as character building and attitude formation in the medical curricula.